NOMINALIZATION IN ACADEMIC ENGLISH: ITS LINGUISTIC FUNCTIONS AND STYLISTIC SIGNIFICANCE - Nurmaxmatova Firuza Rasulovna (TADQIQOTLAR, 2026)
Abstract: Nominalization is a key grammatical feature of academic English. It changes verbs and adjectives into nouns, helping writers express complex ideas clearly and formally. This article looks at the structure, functions, and stylistic impacts of nominalization in academic writing. Relying on systemic functional linguistics, especially the work of M. A. K. Halliday, the study explains how nominalization helps with abstraction, information density, objectivity, and textual cohesion. It also addresses the benefits and drawbacks of too much nominalization, particularly in student writing. The analysis shows that nominalization is more than just a grammatical change; it is a strong rhetorical tool in academic communication.